Primary multifocal cystic signet ring neuroendocrine tumor of liver: a case report - Nalini Bansal; Brahmananda Satapathy (Korean Liver Cancer Association, 2021)
Primary signet ring neuroendocrine tumors of the liver are extremely rare tumors. Morphologically, they mimic signet ring cell adenocarcinomas; however, the absence of mucin by special stains and the expression of neuroendocrine markers help to diagnose these tumors. We herein report a case of a 47-year-old female who presented with multiple solid and cystic lesions in both liver lobes, which were initially suggested to be biliary cystadenocarcinoma on imaging. Liver biopsy of the lesion revealed the presence of a signet ring neoplasm with diffuse expression of synaptophysin and pan-cytokeratin. The case was subsequently diagnosed as a primary hepatic signet ring neuroendocrine tumor. The patient was offered 3 cycles of chemotherapy and is well preserved after 14 months of diagnosis. Although this is an extremely rare entity, its possibility should be considered in the differential diagnosis of neoplasms characterized by signet ring cell morphology.